Capitellum fractures: should the collateral ligament be repaired primarily? - Li, Zonghuan; Yu, Aixi; Zeng, Weijuan (Frontiers in Surgery, 2025)
BackgroundIt is controversial whether the collateral ligaments should be repaired primarily for capitellum fractures with ligamentous injury. This research was conducted to summarize the current evidence for this issue.MethodsDatabases, including Medline, Cochrane library and EMBASE, were searched from their establishment to December 31, 2024 for clinical articles on capitellum fractures. The reference lists of the relevant studies were also checked successively. The general information including first author, publication time, location, the number of cases, treatment for the capitellum fractures with collateral ligament injury, were included. Outcomes, including the pronation and supination of the elbow, active range of motion, Mayo elbow performance score, elbow instability and complications, were extracted.ResultsFifteen studies and 220 patients were identified and analyzed. The average follow-up time ranged from 1.5 to 17 years. The fractures were managed by open reduction and internal fixation. Medial collateral ligaments (MCL) injury was reported in 4 of the 15 included reports. Among the 97 patients, 17 (17.5%) patients suffered capitellum fracture with MCL injury. For the treatment of MCL injury, the literature reports were inconsistent. Nine studies with 159 patients reported the treatment for the lateral collateral ligaments (LCL) injury. Fifty-six cases were complicated with LCL injury, of which 41 cases were primary injury and 15 LCL were released to enhance exposure. All LCL injuries were repaired primarily.ConclusionFor capitellum fractures with ligament injuries, primary repair of LCL should be performed when combined by LCL injury or LUCL release is performed during surgery. The MCL may require primary reconstruction or treatment in a hinged brace.